2011
DOI: 10.1055/s-0030-1250211
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin - Its Potential to Predict and Prevent Coronary Artery Disease

Abstract: Pericoronary fat specifically secretes metabolically active adiponectin. Its local and systemic concentrations are inversely correlated to the presence of coronary artery disease, indicating its anti-atherogenic effects. As for patients with CAD, adiponectin might be a promising marker for intra-individual monitoring of cardiovascular risk factors and thus a course of secondary prevention. Further evaluation is necessary to elucidate whether a novel therapeutic option could be derived against the onset and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The increase in mRNA levels by lycopene was accompanied by an increase in plasma concentration of adiponectin (Figure 1(a)), indicating that the increase in adiponectin plasma concentration could be due an increased adiponectin mRNA synthesis in the adipose tissue. Several studies have shown that the upregulation of adiponectin has antiobesity effects, [3][4][5][6] and lycopene can decrease inflammatory markers [19][20][21]25,27 and reduce obesityrelated complications, such as nonalcoholic steatohepatitis. 33 Thus, this study suggests that the upregulating adiponectin may contribute to the beneficial effects of lycopene.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in mRNA levels by lycopene was accompanied by an increase in plasma concentration of adiponectin (Figure 1(a)), indicating that the increase in adiponectin plasma concentration could be due an increased adiponectin mRNA synthesis in the adipose tissue. Several studies have shown that the upregulation of adiponectin has antiobesity effects, [3][4][5][6] and lycopene can decrease inflammatory markers [19][20][21]25,27 and reduce obesityrelated complications, such as nonalcoholic steatohepatitis. 33 Thus, this study suggests that the upregulating adiponectin may contribute to the beneficial effects of lycopene.…”
Section: Discussionmentioning
confidence: 99%
“…We have taken care to some extent by adjusting for these confounding factors at each stage of the analysis. Another important consideration is that we have measured the levels of total adiponectin as against the high-molecular-weight adiponectin, which some consider as being more metabolic activity than the whole protein (49) with greater biological potency (50,51). Further, we have measured the circulating levels of adiponectin, whereas assessment of adiponectin in the epicardial tissues may tell a different story (52).…”
Section: Biomarkersmentioning
confidence: 99%
“…A number of studies have confirmed that the association between APN and atherosclerosis can regulate glucose and lipid metabolism and increase insulin sensitivity and fatty acid oxidation. APN is associated with the occurrence and development of T2DM, cardiovascular disease and IR (28,29). It has previously been shown that there is a reduction in the levels of APN before the occurrence of diabetes, in first-degree relatives of patients with T2DM (30).…”
Section: Discussionmentioning
confidence: 99%
“…Under conditions of high glucose, the levels of C-reactive protein in the body are elevated, and the reduced plasma APN then accelerates the diabetic vascular disease and prompts the development of atherosclerosis. A study by Skrabal et al (28) showed that APN caused increases in the plasma free fatty acid oxidation and insulin sensitivity, and regulated glucose and lipid metabolism. Thus, APN can modulate the inflammatory response of endothelial cells and inhibit the transformation of macrophages into foam cells, and is associated with the occurrence and development of obesity, IR, T2DM and cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%